2022
DOI: 10.1111/eea.13219
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid venom alters the lipid composition and development of microorganisms on the wax moth cuticle

Abstract: Ectoparasitoids may change host metabolism, making the environment more favorable for the development of their larvae. These alterations may also be suitable for growth and proliferation of commensal microorganisms and pathogens. This is especially important in relation to cuticular microbiota, with which ectoparasitoids interact directly. However, biochemical and microbiological changes occurring on insect cuticles in response to parasitoid venoms are insufficiently understood. We assayed the biochemical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…Previous studies demonstrated that parasitoids do not reject a D. longicaudata-parasitized host before examining it internally with the ovipositor, suggesting that internal conditions or marker pheromones deposited inside the host are responsible for not parasitizing it (Cancino et al, 2012;Devescovi et al, 2020;Montoya et al, 2003). Contrary to the pattern reported in the literature that oviposition by larval parasitoids changes only internal host conditions (Nufio & Papaj, 2001), there is growing evidence that larval parasitism can also induce chemical changes in the host epicuticle (Kryukov et al, 2022;Lebreton et al, 2010). In addition, generalist predators seem to be capable of recognizing parasitized prey on the basis of external cues (Labbe et al, 2006;Moral, Demetrio, et al, 2017;Naranjo, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies demonstrated that parasitoids do not reject a D. longicaudata-parasitized host before examining it internally with the ovipositor, suggesting that internal conditions or marker pheromones deposited inside the host are responsible for not parasitizing it (Cancino et al, 2012;Devescovi et al, 2020;Montoya et al, 2003). Contrary to the pattern reported in the literature that oviposition by larval parasitoids changes only internal host conditions (Nufio & Papaj, 2001), there is growing evidence that larval parasitism can also induce chemical changes in the host epicuticle (Kryukov et al, 2022;Lebreton et al, 2010). In addition, generalist predators seem to be capable of recognizing parasitized prey on the basis of external cues (Labbe et al, 2006;Moral, Demetrio, et al, 2017;Naranjo, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…is the dominant bacterium in the wax moth larvae cuticle, while various Enterobacteria and Pseudomonas spp. may also be dominant or subdominant in host integument (Allonsius et al, 2019; Kryukov et al, 2022). A similar dependence of the parasitoid microbiota on the host's microbiome was observed in the endoparasitic wasp Nasonia vitripennis (Duan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in the present article, the plant- and insect-passaged reisolates demonstrated significantly lowered virulence to two insect species: (a) the wax moth that was used for the passaging and (b) the Colorado potato beetle, which represents a target host from another insect order. Notably, larvae of these two insects possess strikingly dissimilar epicuticular lipid composition ( Tomilova et al, 2019 ; Kryukov et al, 2022 ). In a series of independent studies, it has been reported that passaging through insects may not alter fungal virulence ( Hall, 1980 ; Ignoffo et al, 1982 ; Brownbridge, Costa & Jaronski, 2001 ; Vandenberg & Cantone, 2004 ; Eckard et al, 2014 ; Holderman et al, 2017 ; White et al, 2021 ), and only a few articles indicate its weakening ( Hussain et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%